Therapeutic Potential of Myricitrin in a db/db Mouse Model of Type 2 Diabetes - Sang Ryong Kim; Young-Je Kim; HwiCheol Kim; Sojeong Park; Un Ju Jung (Molecules)
Type 2 diabetes is characterized by insulin resistance, which contributes to dysregulated glucose and lipid metabolism and is associated with chronic inflammation. While previous studies have examined the effects of myricitrin in streptozotocin-induced diabetic models, its impact on the db/db mouse, a model that better reflects insulin resistance-associated metabolic disturbances, remains unclear. In this study, mice were divided into three groups (db/+, db/db, and db/db + 0.02% myricitrin) and were fed their respective diets for five weeks. Myricitrin supplementation reduced fat mass, adipocyte size, and plasma leptin levels, which were elevated in db/db mice. Although myricitrin did not affect fasting blood glucose levels, it lowered plasma insulin, hemoglobin A1c, postprandial glucose levels, and the homeostasis model assessment of insulin resistance, suggesting improvements in insulin sensitivity and glucose homeostasis. Enhanced pancreatic insulin expression, along with reduced hepatic gluconeogenic enzyme activities and mRNA expression, contributed to the improved glucose homeostasis observed in myricitrin-supplemented mice. Additionally, myricitrin reduced hepatic triglyceride levels and lipid droplet accumulation by inhibiting hepatic fatty acid synthase activity. It also decreased plasma inflammatory marker levels and their mRNA expression in adipose tissue. These findings suggest that myricitrin may be a promising therapeutic candidate for type 2 diabetes.